Pediatric Surgery Digest - Zachariou, Zacharias; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This updated volume offers a praxis-oriented and up-to-date overview of all subjects in paediatric surgery according to the European Training Requirements for Paediatric Surgery ( Approved by UEMS in April 2020). Written by experts in the field, Pediatric Surgery Digest aims to give readers quick access to information on all aspects of pediatric surgery, as well as interdisciplinary topics related to paediatrics, adult surgery, obstetrics, and other disciplines working with children. Practical information on child-adapted dosage for pharmacotherapy as well as age-specific injury patterns from scalding in young children to spleen rupture in teenaged vehicle users are taken into consideration. The role of surgery in modern pediatric oncology is also covered.
1. What is Pediatric Surgery? -- 2. Timing of operations in pediatric surgical patients -- 3. Preoperative management -- 4. The newborn as a pediatric surgical patient -- 5. Enteral / Parenteral nutrition -- 6. Emergencies / Resuscitation -- 7. Blood / Blood-products transfusion -- 8. Pain management -- 9. Wounds / Surgical techniques -- 10. Minimal invasive surgery principles -- 11. Imaging in Pediatric Surgery -- 12. Expert opinion -- 13. Special situations -- 14. Birth Trauma -- 15. Skull -- 16. Spinal column -- 16. Face -- 17. Neck -- 18. Thorax -- 19. Diaphragm -- 20. Esophagus -- 21. Abdominal wall -- 22. Abdomen -- 23. Stomach and Duodenum -- 24. Intestinal congenital malformations -- 25. Intestinal diseases -- 26. Anorectal diseases -- 27. Inflammatory bowel diseases -- 28. Blunt abdominal trauma -- 29. Liver and Pancreas -- 30. Liver and Pancreas -- 31. Pediatric surgical oncology -- 32. Urogenital Tract -- 33. Penis -- 34. Testicles -- 35. Vagina and External female genitalia -- 36. Ovarian cysts -- 37. Kidney and Bladder -- 38. Kidney insufficiency -- 39. Skin and Soft tissues -- 40. Osteoarticular system -- 41. Skeletal system -- 42. Embryology -- 43. Vaccinations -- 44. Notifiable infectious diseases -- 45. Fever types -- 46. Catheter sizes -- 47. Reference values -- 48. Commonly used pharmaceuticals -- 49. Syndromes.
Keywords: Surgery; Pediatrics; Urology; Orthopedics; Medical sciences; Surgery; Surgery; Pediatrics; Urology; Orthopaedics; Health Sciences; Surgical Procedures, Operative; Child; Infant; Handbook